Implementation of the Hybrid Flexible-Station Rotation Learning Model on Critical Thinking and Creativity Skills in Elementary Schools in Blitar - Cindya Alfi; Mohamad Fatih (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the effectiveness of the Hybrid Flexible-Station Rotation learning model in enhancing critical thinking and creative abilities in elementary school students. The subjects were 133 class V students in Blitar Regency, divided into two groups: an experimental group using the Hybrid Flexible-Station Rotation model and a control group with conventional learning. The research instruments included pretests and posttests to measure critical thinking and creativity on topics such as stucture of the earth’s layers, water cycles, and shapeof the earth’s surface. The results showed a significant improvement in the experimental group compared to the control group, with an average post-test score of 72.07 for the experimental group and 70.06 for the control group. Paired t-test analysis confirmed a significant difference between the two groups. These findings affirm that the Hybrid Flexible-Station Rotation model is more effective in developing students' critical thinking and creative skills. The study recommends adopting this learning model as an innovative strategy in digital era education.